Pinch Off effect: A lethal Unusual complication of Subclavian Hemodialysis Catheter in a Child - AlbLooshi, Mohammed; Abdulrahman, Dalia; gupta, vipul (Pakistan Journal of Kidney Diseases, 2025)
Pinch-off effect is reported as potential complications of subclavian venous access in 14 years old male child with hemodialysis catheter. Patient presented with features of luminal obstruction 8 months after insertion of hemodialysis catheter. X ray chest confirmed diagnosis of Pinch off syndrome. Replacement of Hemodialysis catheter through supraclavicular subclavian approach resulted in achieving safe and functional venous access for last 12 months.